ANALISIS LAPORAN KEUANGAN DAN INDIKATOR KEBANGKRUTAN UNTUK MENILAI KINERJA KEUANGAN SERTA KELANGSUNGAN PADA PT BAYU BUANA Tbk - Enny Istanti; RM Bramastyo Kusumo Negoro (AKUNTANSI 45, 2021)
In today's tight business competition, many companies always want to stay afloat from business competitors. This research is a qualitative descriptive study with an approach that is carried out using quantitative data calculations in the form of financial statements. From the analysis, it shows that the financial performance of PT Bayu Buana Tbk in 2008 to 2012 can be said to be still not good. Where in terms of liquidity ratios and leverage ratios, the company is still not able to pay off its obligations. For the analysis of bankruptcy indicators, the results obtained from 2008 to 2012, the company is classified as a very healthy company or does not experience financial difficulties or bankruptcy.